Spatial Distribution and Composition of Surface Microplastics in the Southwestern South China Sea - Yu, Jun; Tang, Danling; Wang, Sufen; He, Lei; Pathira Arachchilage, Kalani Randima Lakshani (Frontiers in Marine Science, 2022)
Plastic pollution is one of the growing environmental problems in the world currently. The situation of microplastics (MPs) in the South China Sea (SCS) is not yet fully understood. This study investigated the spatial distribution, morphological characterization, and chemical composition of MPs in surface seawater in the southwestern SCS, based on cruise data in 2018. Our analysis shows that the average abundance of surface MPs in seawater was 0.072 ± 0.053 particles/m3 and 88.4% of MPs were <2 mm. 97.3% of MPs were fibers and fragments. Polyethylene terephthalate (PET), polyvinyl chloride (PVC), and cellophane were predominant polymer components of surface MPs. Higher MPs abundance (0.083 ± 0.063 particles/m3) and bigger MPs sizes were found at surface water in Nansha Islands than in Xisha Islands (0.032 ± 0.01 particles/m3). In addition, more polymer types of MPs were found in Nansha Islands, while more MPs films were found in Xisha Islands. PET and cellophane dominated in Nansha Islands, while PVC dominated in Xisha Islands with no cellophane detected. The surface MPs were low in abundance and diverse in polymers in the southwestern SCS with apparent differences between islands and between onshore and offshore, owing to plastics wastes from vessel traffics and some inhabited islands.